Going Serverless with AWS Athena, Data as a service - George Paul OPRESCU (Communications of International Proceedings, 2020)
An e-commerce platform is not just a web page with buttons and text that can be easily controlled. In addition to the economic factors and the field in which it operates, the technologies behind the platform are critical in its development. Maintenance involves costs, and they vary depending on the complexity of the data storage services. The layout of the page is also essential, but in order to develop it, a favorable environment for storing data and information is needed. It is essential to know how data is being transformed for analysis and statistics that facilitate business decisions. Most applications use a relational database, the most common being SQL Server from Microsoft. This database is physically stored on virtual machines alongside the application. There is the possibility of having a virtual machine for each application, but in the presence of several applications, users can experience an increase in costs. Kubernetes allows an application to start a virtual machine only when it is being used, resulting in low maintenance costs. However, the future does not consist of virtual machines and servers, cloud services from Amazon being much more efficient. Data and information are stored in the cloud, being exposed to the customer whenever he needs them. Data is then intelligently transformed into statistics and business information through various, almost autonomous data streaming and business intelligence tools.
Keywords: Amazon Web Services; Amazon Athena; Artificial Intelligence; S3 Buckets; Data-as-a-service; Big Data; Cloud Computing; PostgreSQL.